(untitled) (Brazilian Journal of Police Sciences, 2026)
Knowing the performance of the police is necessary for the accountability of these organizations, seeking effectiveness, efficiency and effectiveness, which is in line with the paradigm established by the New Public Management (NPM). However, even with the paradigm shift in the context of public security policies that took place in the country in the last decade, it is still possible to verify that low quality management of the efficiency and effectiveness of organizations that work in the criminal sphere persists, especially in police. The theoretical essay presents the context of the performance evaluation of the Brazilian judicial police, evidencing the need to establish an agenda to discuss, research and create tools that allow monitoring and managing the performance of these organizations, in order to assist in the improvement of their actions, resulting in the rationalization of public resources and the improvement of services provided, as proposed by NPM. Assessing the performance of the judicial police is a necessary agenda in the country, which can encourage the beginning of a culture of performance assessment in these and other organizations that make up the country’s public security system. In this sense, the NPM presents itself with a set of tools that can contribute to the improvement of the performance management of the Brazilian judicial police.